Evaluation of User Satisfaction of Electronic Medical Record System at RSI Sultan Agung Semarang - Lutfiyah Rizqulloh; Muhammad Iqbal; Diah Kurniawati (Window of Health : Jurnal Kesehatan, 2025)
From 2019 to 2022, RSI Sultan Agung Semarang managed SIMRS independently. While the implementation remained hybrid, SIMRS was turned over to a third party in early 2023 to develop Electronic Medical Records (EMR). However, in 2024, a year later, the management of SIMRS and EMR was once again independent. It was necessary to assess user satisfaction with the EMR in light of these modifications. This study aims to determine the variables affecting users' satisfaction with the EMR at RSI Sultan Agung Semarang's medical record installation. Cross-sectional research was used in conjunction with quantitative research design. Questionnaires were distributed to collect data. Purposive sampling was used in the sampling process, and 32 individuals met the inclusion criteria. The statistical test results demonstrate that all of the variable's content, accuracy, format, ease of use, and timeliness have p-values less than 0.05, indicating a significant relationship between each variable and satisfaction with the EMR. Everything about the EMR system has been going smoothly; more system development is needed to make it easier to access quickly and effectively, which will improve the timeliness of medical services. Future research should look into other variables or perform long-term studies to track changes in user satisfaction.